An Epichloë endophyte improves photosynthetic ability and dry matter production of its host Achnatherum inebrians infected by Blumeria graminis under various soil water conditions. (August 2016) - Xia, Chao; Li, Nana; Zhang, Xingxu; Feng, Yao; Christensen, Michael J.; Nan, Zhibiao
Abstract: The interaction between an Epichloë endophyte, Blumeria graminis and Achnatherum inebrians, was studied at four soil water contents. Lesion length and disease index were recorded dynamically, and the chlorophyll content, photosynthetic parameters and final dry matter accumulation were measured after a 4-week period of disease. Infection by B. graminis significantly (P < 0.05) decreased the chlorophyll content, net photosynthetic rate, intercellular carbon dioxide concentration and dry matter at some soil water contents. Presence of the endophyte lowered the disease index while significantly (P < 0.05) increasing the chlorophyll content and net photosynthetic rate. The endophyte also positively affected the intercellular carbon dioxide concentration. In addition, it increased the dry matter accumulation per host plant under pathogen stress. The study demonstrated that while powdery mildew depresses the photosynthetic parameters of A. inebrians, the presence of the Epichloë endophyte can reduce the damage caused by the pathogen.